2006
DOI: 10.1590/s0102-311x2006000400014
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the AIDS epidemic among injection drug users in Brazil

Abstract: The HIV/AIDS epidemic among injection drug users (IDUs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
20
0
4
Order By: Relevance
“…The data on the method of transmission of HIV-1 confirm those found in the other regions of the country, in which sexual relations was predominant 19,20 , especially among individuals with a low level of education. Intestinal parasite infection presents a problem among HIV-1 patients because of the decreased immunity and the infestation by pathogenic microorganisms, which may result in diarrhea 20,21 . Data on the LTCD4 + count were found only in some forms; therefore, no inference could be made.…”
Section: Resultsmentioning
confidence: 99%
“…The data on the method of transmission of HIV-1 confirm those found in the other regions of the country, in which sexual relations was predominant 19,20 , especially among individuals with a low level of education. Intestinal parasite infection presents a problem among HIV-1 patients because of the decreased immunity and the infestation by pathogenic microorganisms, which may result in diarrhea 20,21 . Data on the LTCD4 + count were found only in some forms; therefore, no inference could be made.…”
Section: Resultsmentioning
confidence: 99%
“…In the south of the country, the epidemics among injecting drug users appear not to be abating (Hacker et al, 2006). Meanwhile, a cross-sectional study in the states of Bahia, Rio Grande do Sul and Sao Paulo, has found that 37% of injecting drug users were infected with HIV, and those infection levels were significantly associated with incarceration and having unprotected sex with other men (Caiaffa et al, 2006).…”
Section: Outbreaks Of Hiv Are Occurring Among Injecting Drug Users Anmentioning
confidence: 99%
“…10 Due to specifi c patterns of cocaine use -constant and repetitive use in a single day -active cocaine users frequently engage in risk behaviors to maintain their patterns of consumption. 11,12 Some studies have also reported the transition toward crack cocaine of former cocaine snorters and/or injectors in Brazil.…”
Section: Introductionmentioning
confidence: 99%